Severe atypical herpes zoster as an initial symptom of fatal myelodysplastic syndrome with refractory anemia and blast excess (RAEB II) - Wollina U; Hansel G; Baunacke A; Tchernev G (Dove Medical Press, 2017)
Uwe Wollina,1 Gesina Hansel,1 Anja Baunacke,1 Georgi Tchernev2 1Department of Dermatology and Allergology, Academic Teaching Hospital Dresden-Friedrichstadt, Dresden, Germany; 2Department of Dermatology and Dermatologic Surgery, Medical Institute of Ministry of Interior (MVR), Sofia, Bulgaria Abstract: Herpes zoster is a common disease caused due to varicella zoster virus (VZV) infection with increasing incidence by age. If the patient has a severe, extended, or treatment-recalcitrant course of herpes zoster, this must be a red flag to search for underlying pathologies. Here, we report about a 64-year-old male patient with diabetes, who came to our emergency department because of general malaise, fever, chills, and a pronounced nuchal and facial swelling on the left side. Based on herpetiform-grouped vesicles and yellowish crusts, an impetiginized facial herpes zoster was diagnosed, and combined antiviral and antibiotic treatment was initiated. He was HIV negative. Despite intensified treatment, his situation worsened. We observed blasts in peripheral blood, but bone marrow biopsy was initially denied. Some days later after deterioration of his disease, he accepted further diagnostics. A myelodysplastic syndrome with blast excess (refractory anemia and blast excess II, RAEB II) could be confirmed. The following translocations were detected: t(2;12)(p13; q13) and t(6;9)(p22;q34). REAB II has an unfortunate prognosis. Cytoreductive treatment was initiated by the hemato-oncologist. Unfortunately, the patient deceased due to septic shock. Keywords: herpes zoster, varicella zoster virus, myelodysplastic syndrome, sepsis, emergency